2010
DOI: 10.9755/ejfa.v22i4.4878
|View full text |Cite
|
Sign up to set email alerts
|

Salt tolerance classification in wheat genotypes using reducing sugar accumulation and growth characteristics

Abstract: Abstract:The aim of the present study was to assess inter and intra-specific variations in Triticum groups. Local hexaploid bread wheat and Synthetic Elites and Durum where characterized based on growth abilities and amount of reducing sugar accumulated under 200 mM NaCl salinity. Further, the role of reducing sugar accumulation in adaptive process of different Triticum groups towards salinity was also measured. Identification of inter-specific and intra-specific variation with in the gene pool is of greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Our observations are in accordance with the conclusions of Agamy et al, (2013) in tomato. Naureen & Naqvi (2010) reported that increased carbohydrate levels under salt stress could be suitable parameters for identifying salt-tolerant wheat plants. This increase in total carbohydrate levels is a mechanism of osmoregulation ( Siringam et al, 2012;Shaddad et al, 1990), and is involved in protecting plants from oxidative stress and maintaining the structures of proteins and membranes as well (Hajihashemi et al, 2006).…”
Section: Sa Application Improves the Synthesis Of Proline Free Aminomentioning
confidence: 99%
“…Our observations are in accordance with the conclusions of Agamy et al, (2013) in tomato. Naureen & Naqvi (2010) reported that increased carbohydrate levels under salt stress could be suitable parameters for identifying salt-tolerant wheat plants. This increase in total carbohydrate levels is a mechanism of osmoregulation ( Siringam et al, 2012;Shaddad et al, 1990), and is involved in protecting plants from oxidative stress and maintaining the structures of proteins and membranes as well (Hajihashemi et al, 2006).…”
Section: Sa Application Improves the Synthesis Of Proline Free Aminomentioning
confidence: 99%
“…Thus, the up-regulation of photosynthetic pigments in broad bean could increase the efficiently of photosynthetic apparatus in broad bean which leads to increasing the food manufacturing (carbohydrates and proteins) in broad bean than in wheat. Other investigators, [38] reported that, the increased carbohydrate contents under salt stress could be good parameter to identify salttolerant wheat plants. This increasing in the total carbohydrate contents act as osmoregulation mechanism [39,40] and also it used to protect the plants from oxidative stress and maintain the protein and membrane structure [41].…”
Section: A) ) B) )mentioning
confidence: 99%
“…However, V. luteola and T44 (relatively tolerant) retained higher content of nonreducing sugar content than PB (relatively susceptible). However Naureen and Naqvi (2010) reported that salinity stress of 200 mM significantly increased the amount of nonreducing sugar in wheat.…”
Section: Sucrose Synthasementioning
confidence: 98%